Neue Orte für die Götter: Zu Lokalisierungsdynamiken von tamilischer Hindu-Praxis in der Schweiz - Eulberg, Rafaela (Culturel, 2022)
Since the 1980s, Tamil refugees from Sri Lanka and their descendants have been practicing Hindu traditions in diaspora countries such as Switzerland. Based on ethnographic research, the author analyses processes involved in establishing Tamil Hindu practice. The aim is to provide a comprehensive insight into the different consecutive phases of how Tamil Hindus have made Switzerland their home. In the formation of sacred spaces and the presentation of Tamil Hindu practices in public, references to the country of origin and transnational networks of the Sri Lankan Tamil diaspora as well as the conditions for incorporation in the country of residence, Switzerland, play a central role. The study focuses in particular on places, their dynamics and the associated performances. Thereby, the importance of self-managed temples as sensual, multifunctional perceptual spaces for the marginalised Tamil Hindu migrants is made clear. Through creative processes of adaptation new forms of religious practice emerge